Systematic selection of blockchain platforms using Fuzzy AHP-TOPSIS / Shahr Banoo Muradi - Shahr Banoo , Muradi (2022)
Various businesses and industries such as financial, medical care management, supply chain management, systematic instruction, data management, fundraising platforms, Internet of Things (IoT) and government supremacy, have been using blockchain technology to develop systems. Similar to other technologies, despite the superiority it holds, some shortcomings and issues accompany the adoption of Blockchain. interoperability challenges, security attacks, sustainability, latency, availability issues related to blockchain performance and scalability are listed as the most critical challenges standing against its vast adoption. If the blockchain platform is not properly selected, the functionality and quality of the blockchain-based systems could be biased. Furthermore, choosing the right platform that best meets the project requirements and targets is getting complicated due to the availability of numerous blockchain platforms with unique properties and specifications. For this, the design of a systematic selection method that contributes decision-makers toward a suitable blockchain platform choice is highly desirable. During the selection of blockchain platforms, many criteria need to be taken into account depending on the organization, project and use case requirements. If the selection criteria are derived carefully concerning the specified factors, the effectiveness and feasibility of the selection method will be enhanced. This research proposes a set of selection criteria that cover both features and quality attributes of the blockchain platforms. A systematic selection method is proposed based on the Fuzzy AHP-TOPSIS approach which compares and select alternative blockchain platforms against the selection criteria. Three industrial cases were used to prove the accuracy of the ranked list of alternatives generated by the proposed selection method. Additionally, an evaluation by blockchain experts was performed and the results show that the proposed selection method can be applied practically to support the decision-makers in blockchain platform selection for real-world projects.